Gibberellin-related genes regulate dwarfing mechanism in wintersweet - Zhu, Ting; Liu, Bin; Liu, Ning; Xu, Jie; Song, Xingrong; Li, Shuangjiang; Sui, Shunzhao (Frontiers in Plant Science, 2022)
Chimonanthus praecox (wintersweet) is an important cut flower and pot plant with a high ornamental and economic value in China. The development of dwarf wintersweet varieties has become an important research topic for the wintersweet industry. The lack of natural dwarf germplasm has hindered research into the molecular mechanisms of developing dwarf wintersweet, limiting its cultivation. After a long-term investigation and collection of germplasm resources of C. praecox, we obtained the germplasm of a dwarf C. praecox (dw). Here, the dwarf (dw) and normal C. praecox (NH) were used to identify the types of hormones regulating dw formation using phenotypic identification and endogenous hormone determination. Differentially expressed genes in the dw and NH groups were screened using transcriptome analysis. The functions of key genes in the dwarf trait were verified by heterologous expression. It was found that the internode length and cell number were significantly reduced in dw than in NH, and the thickness of the xylem and pith were significantly decreased. The dwarfness of dw could be recovered by exogenous gibberellic acid (GA) application, and endogenous GA levels showed that the GA4 content of dw was substantially lower than that of NH. Transcriptome differential gene analysis showed that the elevated expression of the CpGA2ox gene in the GA synthesis pathway and that of CpGAI gene in the signal transduction pathway might be the key mechanisms leading to dwarfing. Combined with the results of weighted gene co-expression network analysis, we selected the CpGAI gene for analysis and functional verification. These results showed that CpGAI is a nuclear transcriptional activator. Overexpression of CpGAI in Populus tomentosa Carr. showed that CpGAI could lead to the dwarfing in poplar. We analyzed the dwarfing mechanism of C. praecox, and the results provided a reference for dwarf breeding of wintersweet.